NEXUS Gains Talk 9: The Future of Water Research - Smith, Mark (CGIAR System Organization, 2023)
Ahead of the UN 2023 Water Conference, this NEXUS Gains talk previewed eight missions developed as part of the Transformative Futures for Water Security (TFWS) dialogues.